2016
DOI: 10.2196/mhealth.4509
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the Feasibility and Practicalities of Text Messaging-Based Infectious Disease Surveillance: A Questionnaire Survey

Abstract: BackgroundIn Vietnam, infectious disease surveillance data are collected via a paper-based system through four government tiers leading to a large delay. Meanwhile, mobile phones are abundant and very popular in the country, and known to be a useful tool in health care worldwide. Therefore, there is a great potential for the development of a timely disease surveillance system through the use of mobile phone short message service (SMS) text messages.ObjectiveThis study aims to explore insights about the feasibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…After duplication removal and screening, 27 records met inclusion criteria, which were sorted into 10 initiatives (Initiative #1, 4, 6, 7, 10, 11, 13, 16, 17, and 20). Of these 27 records, there were 12 research papers [ 13 , 14 , 22 - 31 ], 8 conference presentations [ 32 - 39 ], 2 Vietnamese governmental documents [ 40 , 41 ], 2 graduate dissertations [ 42 , 43 ], 2 case studies [ 44 , 45 ], and 1 project technical report [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After duplication removal and screening, 27 records met inclusion criteria, which were sorted into 10 initiatives (Initiative #1, 4, 6, 7, 10, 11, 13, 16, 17, and 20). Of these 27 records, there were 12 research papers [ 13 , 14 , 22 - 31 ], 8 conference presentations [ 32 - 39 ], 2 Vietnamese governmental documents [ 40 , 41 ], 2 graduate dissertations [ 42 , 43 ], 2 case studies [ 44 , 45 ], and 1 project technical report [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…As of May 2017, Vietnam had about 58.9 million Internet users, which is more than half of the population [ 12 ]. SMS text messaging (SMS, short message service) is inexpensive and mobile phone service coverage is wide (eg, [ 13 , 14 ]).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of SARS‐CoV‐2, the symptoms with the greatest sensitivity are: fever (98.6%), fatigue (69.6%), dry cough (59.4%), myalgia (34.8%), and dyspnea (31.2%) 18 . Large‐scale population studies suggest that self‐reported disease symptomatology has moderate‐to‐high concordance with clinical diagnosis 19–21 . Recording clinical signs of disease is another method to distinguish potentially infectious patients.…”
Section: Elimination and Substitutionmentioning
confidence: 99%
“…In Latin America, the unsuitability of Google Flu Trends to accurately predict influenza outbreaks across countries has been attributed to low Internet penetration rates and to heterogeneous usage of search engines among non-English speaking populations [ 24 ]. Alternatively, the ubiquity of feature phones—a midway point between smartphones and basic mobile phones [ 25 ], which are only capable of voice calling and text messaging—coupled with the increasing penetration of smartphones provides culturally relevant infrastructure opportunities to capture health information with the use of apps and short message service (SMS) (or text messages) [ 26 , 27 ]; it is almost four times more likely to be a mobile phone user than an Internet user in Central America (34 Internet users per 100 people [ 28 ] vs 130 mobile subscriptions [ 29 ] per 100 people). No published studies to date have assessed the viability of ILI surveillance with mobile-based tools in the region.…”
Section: Introductionmentioning
confidence: 99%